UPAYA PENINGKATAN KINERJA PEGAWAI PASCA COVID 19 DI KANTOR SEKRETARIAT DAERAH KABUPATEN TEMANGGUNG - Iin Novitasari; Uswatun Chasanah (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
This research aims to improve employee performance after Covid-19 at the Regional Secretariat of Temanggung Regency. The research was carried out starting in October 2022. This type of research is descriptive qualitative. Collection of interview and observation data. Miles and Huberman Model data analysis. The results showed that: 1) The performance of the employees of the Regional Secretariat of the Temanggung Regency after Covid 19 was not optimal due to the level of attendance, quality of work, quantity of work, activities were partially cut and diverted to handling Covid so that it had an impact on field activities and limited official social interaction. 2) The factors that cause employee performance are not optimal, namely: planning that is not in accordance with implementation due to budget diversion for Covid-19, weak commitment to individuals, lack of coordination, lack of employee motivation because compensation received is only in the form of salary, lack of supervision and control, WFH habits that are still attached make a lack of discipline. 3) Efforts to improve employee performance, namely: making plans according to implementation, increasing employee commitment, increasing coordination between superiors and subordinates, increasing employee motivation, increasing supervision, control and evaluation as well as implementing reward and punishment by giving awards to employees who excel and sanctions for employees who break the rules.